2022
DOI: 10.1371/journal.pone.0269880
|View full text |Cite
|
Sign up to set email alerts
|

Aedes koreicus, a vector on the rise: Pan-European genetic patterns, mitochondrial and draft genome sequencing

Abstract: Background The mosquito Aedes koreicus (Edwards, 1917) is a recent invader on the European continent that was introduced to several new places since its first detection in 2008. Compared to other exotic Aedes mosquitoes with public health significance that invaded Europe during the last decades, this species’ biology, behavior, and dispersal patterns were poorly investigated to date. Methodology/Principal findings To understand the species’ population relationships and dispersal patterns within Europe, a fra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…Meanwhile, the Belgian and Italian populations likely originated from Jeju Island (Capelli et al 2011, Versteirt et al 2012b). These findings are consistent with those of Kurucz et al (2022), who analyzed mitochondrial cytochrome oxidase I and found that Ae. koreicus populations in Belgium and Italy belong to the Jeju Island population.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, the Belgian and Italian populations likely originated from Jeju Island (Capelli et al 2011, Versteirt et al 2012b). These findings are consistent with those of Kurucz et al (2022), who analyzed mitochondrial cytochrome oxidase I and found that Ae. koreicus populations in Belgium and Italy belong to the Jeju Island population.…”
Section: Introductionsupporting
confidence: 93%
“…In contrast, the German population came from the Korean Peninsula. Therefore, it appears that each population has invaded Europe at least once (Kurucz et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although some information about genome organisation has been very partially provided for Ae. koreicus (Kurucz et al, 2022), a more detailed knowledge of the basic biology of the new European invasive species Ae. koreicus and Ae.…”
Section: Rnaseq Analysis Of Thermal Adaptation Genesmentioning
confidence: 99%
“…After its first detection in Belgium in 2008 (Versteirt et al, 2012), the mosquito Aedes koreicus ( Hulecoetomyia koreica ), commonly known as the invasive Korean bush mosquito, has invaded and established in several states in Europe and European neighbouring countries (ECDC, 2022). In some areas, such as Italy, the species is currently expanding its distribution (Arnoldi et al, 2022), but in others, such as Germany, it has shown a relatively low tendency to spread despite suspected repeated introductions (Kurucz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%